SURGICAL COUNTS CAN BE RISKY BUSINESS! - Porteous, Joan (Operating Room Nurses Association of Canada Journal, 2004)
The surgical count plays a vital role in enabling perioperative nurses to provide a safe environment to surgical patients. Counting errors are preventable. Although national standards of care provide excellent guidelines for developing effective count protocols, counting procedures are often modified according to individual health care policy. This article will discuss the risk factors for retained items, rate of occurrence, what objects are being left in patients, role of x-rays and consequences of leaving an object in a patient. It will also highlight points to be considered when implementing new count policies.